Metodologia de projeto de fontes ininterruptas de energia monofásicas empregando controladores de ação repetitiva auxiliar no estágio de saída - Michels, Leandro (2006)
The present doctoral thesis concentrate efforts in the consolidation of the benefits introduced by the plug-in repetitive action in the performance of pulse-width modulated voltage source inverters. The work is focused in the application of these inverters in double conversion uninterruptible power systems to comply the most demanding requirements of the international standards. The use of the plug-in repetitive action, in this application, is suitable because the inverter demands the advantageous characteristics of cyclic disturbance rejection by it introduced. In this scenario, this thesis is divided in two parts. The first one comprise the proposition of algorithms to solve some disadvantageous characteristics of the repetitive actions, such as the reduced stability margin and the unsuitable performance under reference signals with variable frequency. The second one, by the other hand, comprise the questions related to the design of these repetitive action controllers. It is included the proposition of a methodology that link the design of these controllers with the output filter of a double conversion UPS. Finally, it is worth to emphasize that are presented simulation and experimental results, obtained on a 1kVA laboratory prototype, that validate the proposes carried out.